Revolutionary Collective Comrades, Critics, and Dynamics in the Struggle for Socialism. - Le Blanc, Paul, 1947- (Haymarket Books, 2022)
This important volume traces efforts to advance the socialist goal through the organization of revolutionary collectives, engaging with a pantheon of relevant radical thinkers.